Numerical and experimental studies of gas flow in a particulate filter. (14th December 2019) - Cooper, J.D.; Liu, L.; Ramskill, N.P.; Watling, T.C.; York, A.P.E.; Stitt, E.H.; Sederman, A.J.; Gladden, L.F.
Graphical abstract: Highlights: MRI measurements made of gas velocities in a real DPF for Re = 102–1251. Validation of 3D CFD predictions of gas velocity in a DPF geometry. Comparisons of calculated model parameters with previous literature correlations. 1D model predictions coincident with 3D CFD with correct descriptors. Abstract: Predicted gas flow fields in wall-flow particulate filters, used for vehicular emissions abatement, from both one- and three-dimensional numerical models have been validated for the first time. This has been achieved using experimental measurements made using magnetic resonance imaging (MRI). Two-dimensional MRI velocity images of isotropic spatial resolution 140 µm px −1 were acquired perpendicular to the filter channels at multiple points, allowing measurement of the gas axial velocity in both the inlet and outlet channels along the length of the filter. Consideration of the mass balance between data points permitted the through-wall (i.e. filtration) velocity to also be calculated. These velocity data were acquired at six flow rates, corresponding to channel Reynolds numbers in the range 102–1251, and compared with the predictions from both an open source three-dimensional CFD code and a recent one-dimensional model. Good agreement was observed for both models at low flow rates, but the three-dimensional model outperformed the one-dimensional model at higher flow rates. The validation of the 3D CFD method allowed its use to probe local gas hydrodynamics, specifically calculating the variation of the momentum convection correction factor and wall friction factor. Comparisons of the calculated factors and literature correlations showed the effects of flow development are significant and have not previously been considered. When these correlations were used with the 1D model, the velocity predictions were coincident with those of the 3D CFD. Hence, with the appropriate flow descriptors, the 1D model can be used to give accurate gas velocity predictions but at a fraction of the computational time required to run CFD code.